Approaching to ethical-moral thinking of scientists working with experimental animals - Concepción Alfonso, Ángel R.; de la Peña Pino, R.; García Capote, J. (Acta Bioethica, 2007)
The vertiginous advance of the scientific technical revolution and the use not always rational and ethical of animals in research, has provoked that many researchers worry about the future of animal species used, which has been the topic of many studies in the last decade. Multiple regulations have been formulated and the application of ethical principles in research has been considered. This paper considers the use of alternative methods in research with animals whenever possible, reviews the principle of the three Rs and other related aspects and reflect on the responsibilities of the scientist with the end product of his/her results.